2022
DOI: 10.3390/land11111890
|View full text |Cite
|
Sign up to set email alerts
|

How Do the Different Types of Land Costs Affect Agricultural Crop-Planting Selections in China?

Abstract: Land costs in agricultural production are rapidly becoming apparent and increasing in light of the market’s rapid development in rural China. This study examines how agricultural operators’ farming decisions are affected by explicit and implicit costs associated with land transfers. This study first categorizes explicit and implicit land costs theoretically and demonstrates that both types of land costs affect farmers’ crop-planting selections. The study then uses the most recent household survey data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This is to say, owning more pieces of arable land in the rural area can secure the farming careers of heirs. In addition to this advantage, having a variety of mixed farming products and activities, such as various kinds of plants and vegetables, livestock farming, or fisheries, increases the chance of inheriting the farming career, ensures the sustenance of farming in the long term, and secures the economy through several income sources, similar to the findings in [31,32]. All these noteworthy points may create the possibility for an heir to choose the faming career, as determined by the will of the parents, in order to continuously secure their income through various sources.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This is to say, owning more pieces of arable land in the rural area can secure the farming careers of heirs. In addition to this advantage, having a variety of mixed farming products and activities, such as various kinds of plants and vegetables, livestock farming, or fisheries, increases the chance of inheriting the farming career, ensures the sustenance of farming in the long term, and secures the economy through several income sources, similar to the findings in [31,32]. All these noteworthy points may create the possibility for an heir to choose the faming career, as determined by the will of the parents, in order to continuously secure their income through various sources.…”
Section: Discussionmentioning
confidence: 64%
“…Having a positive attitude towards the farming career can clearly strengthen the survival of family farms [4]. The reports of the International Fund for Agricultural Development [29] and the study reported in [30][31][32] reached the same conclusion, stating that the family's land size is one of the most important factors necessary to sustain the succession of family farming. Having a section of arable land in a rural area can encourage the continuation of farming activities [33][34][35][36].…”
Section: Tool and Data Collectionmentioning
confidence: 79%
“…There are many explanations for this conclusion, but the most critical crux is the high cost of land transfer, and the root cause is the low comparative returns of grain crops [60]. According to the data of the National Compilation of Costs and Benefits of Agricultural Products [61], from 2003 to 2020, the average land rent of the three main grain crops (paddy, wheat, and maize) in China increased from 56.1 CNY/hectare to 660.15 CNY/hectare, an increase of 10.8 times.…”
Section: Explanation Of the Results Of This Studymentioning
confidence: 99%
“…The domestic water resources saved by the SEFI can produce fewer low-water-use food crops. Therefore, the SEFI has a less negative impact on the proportion of WFC in non-major food-producing areas than in major ones [31]. Table 6.…”
Section: Heterogeneity Analysismentioning
confidence: 98%